Seasonal variations in physico-chemical characteristics of Ravivar Peth Lake at Ambajogai District. Beed Marathwada Region, India. - Raut KS; SE, Shinde; TS, Pathan; DL, Sonawane (Journal of Research in Biology, 2011)
The present study deals with the assessment of water quality of the Ravivar Peth Lake, Dist. Beed Marathwada Region, India. The physico-chemical characteristics were studied and analyzed during January – December of the year 2004. Seasonal variations at three different sampling sites of the Ravivar Peth Lake were observed Conductivity, pH, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Nitrate, Sulphate and Phosphate were studied at these studies. The results revealed that the condition of this lake in different seasons showed fluctuations in physico-chemical parameters and showed pollution status of this lake